2009
DOI: 10.1123/tsp.23.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Cohesion by Youth Sport Participants

Abstract: Cohesion is an important small group variable within sport. However, the conceptualization and examination of cohesion have predominately been oriented toward adult populations. The purpose of the current study was to garner an understanding of what cohesion means to youth sport participants. Fifty-six team sport athletes (Mage = 15.63 ± 1.01 years) from two secondary schools took part in focus groups designed to understand participants’ perceptions of (a) the definition of cohesion and indicators of cohesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
2
41
0
8
Order By: Relevance
“…It was believed that the analysis of previously conducted studies examining children and youth sport (e.g., Eys et al, 2009a;Eys, Loughead, Bray, & Carron, 2009b;McCarthy, Jones, & Clark-Carter, 2008;Ulrich-French & Smith, 2009; would help in item generation.…”
Section: Methods Phase 1: Children's Perceptions Of Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was believed that the analysis of previously conducted studies examining children and youth sport (e.g., Eys et al, 2009a;Eys, Loughead, Bray, & Carron, 2009b;McCarthy, Jones, & Clark-Carter, 2008;Ulrich-French & Smith, 2009; would help in item generation.…”
Section: Methods Phase 1: Children's Perceptions Of Cohesionmentioning
confidence: 99%
“…Recent research with younger populations (ages 13-17) however, contributes to the suggestion that youth do not necessarily perceive cohesion in the same way as adults (Eys, Loughead, Bray, & Carron, 2009a;Eys, Loughead, Bray, & Carron, 2009b). Eys and colleagues found that although youth participants could easily understand and discuss aspects of cohesion, they did not perceive the four-factor structure advanced by Carron and his colleagues (Carron et al, , 2002.…”
Section: T Gi-s Atg-t and Atg-s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Observa-se na literatura que os avanços das pesquisas em relação à coesão de grupo estão relacionados a estratégias de intervenção ao longo da temporada 6 , liderança do treinador 7,8 , eficácia coletiva 9 , desempenho 10 , satisfação de atletas 11 e ansiedade 12 . Enquanto que as pesquisas voltadas ao estresse têm se relacionado com diferentes modalidades coletivas e individuais 13,14 , estratégias de coping 15,16 , jovens atletas 17 e overtraining 18 .…”
Section: Introductionunclassified
“…O presente estudo tem como base teórica o modelo conceitual de coesão no esporte de Carron et al 19 , o qual aponta que a coesão de grupo pode ser influenciada negativa ou positivamente pelos aspectos psicológicos individuais dos atletas, como o estresse psicológico pré-competitivo 12 . Considerando que o estresse pode interferir na coesão de grupo e no desempenho do atleta, evidencia-se a relevância de estudos que abordem estas duas variáveis 3,20 .…”
Section: Introductionunclassified